Analisis Faktor yang Berhubungan dengan Kejadian Anemia Pada Ibu Hamil - Sari, Intan; Aquari, Bina (JOURNAL OF MIDWIFERY SCIENCE, 2024)
Anemia in pregnancy is a global health issue, with higher prevalence in developing countries compared to developed ones. In Indonesia, the prevalence reaches 63.5%, while at the Annisa Maternity Clinic in Banyuasin, 28 cases were recorded in 2023. Risk factors for anemia in pregnant women include age, parity, pregnancy spacing, education, knowledge, nutritional status, socioeconomic status, and adherence to iron tablet (Fe) consumption. The aim of this study is to determine the factors associated with the incidence of anemia among pregnant women at the Annisa Maternity Clinic Banyuasin in 2024. This research used an analytic survey with a cross-sectional design involving 40 pregnant women who underwent antenatal care at the clinic in February 2024. Samples were taken using accidental sampling technique. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test (α = 0.05). The results showed that 37.5% of respondents experienced anemia. High-risk age among pregnant women was 37.5%, low education was 45.0%, and poor knowledge was 42.5%. The study found a significant relationship between age, education, and knowledge with the incidence of anemia among pregnant women at the Annisa Maternity Clinic Banyuasin in 2024.Based on these findings, researchers hope that healthcare providers can enhance antenatal care (ANC) services at the Annisa Maternity Clinic and more frequently conduct educational sessions on anemia during pregnancy.